Boosting interfacial charge transfer by constructing rare earth–doped WOx nanorods/SnO2 hybrid electron transport layer for efficient perovskite solar cells. (September 2021) - Chen, X.; Shi, Z.; Pan, G.; Zhu, J.; Hu, J.; Wu, Y.; Tian, Y.; Li, X.; Xu, W.
Abstract: Recently，the highest power conversion efficiency (PCE) of perovskite solar cells (PSCs) is up to 25%. Interfacial engineering strategy is an efficient route for improving carrier extraction and transport in planar heterojunction PSCs. Herein, we use the rare earth (RE)-doped WOx nanorods/SnO2 hybrid films as the electron transport layer (ETL) to accurately modulate the interfacial charge dynamics for hysteresis-free, high-performance devices. The RE-WOx nanorods with SnO2 can improve the perovskite crystal quality and hinder electron-hole recombination by reducing the interface traps/defects between the ETL and perovskite. Meanwhile, owing to the excellent mobility and conductivity of RE-WOx nanorods and the well gradient band alignment, the improved electron extraction and transport at the interface of ETL and perovskite in PSCs are obtained compared with the SnO2 ETL. With these desirable properties, the optimized PSC device yields a high PCE of 21.42% with negligible hysteresis. Meanwhile, the stability of PSC devices could also be significantly boosted without any encapsulation. The introduction of RE-WOx nanorods as the interface modifier is a significant strategy to improve the interface property in the PSCs and opens up a novel and promising avenue for application in efficient and stable PSCs. Graphical abstract: Image 1 Highlights: An interfacial engineering strategy based on hybrid ETL is proposed for efficient perovskite solar cells. The interface traps/defects at perovskite/ETL interfaces in PSCs could be efficiently suppressed. The rare earth–doped WOx nanorods facilitate the electron extraction and transport efficiency. The champion PCE of the planar PSCs is boosted to 21.42% with long-term ambient stability.